Arginine Vasotocin and Cortisol Co-regulate Vasotocinergic, Isotocinergic, Stress, and Thyroid Pathways in the Gilthead Sea Bream (Sparus aurata) - Martos-Sitcha, Juan Antonio; Cádiz, Laura; Gozdowska, Magdalena; Kulczykowska, Ewa; Martínez-Rodríguez, Gonzalo; Mancera, Juan Miguel (Frontiers in Physiology, 2019)
In teleosts, a complex interaction between several endocrine axes modulates physiological functions related to metabolism, stress and osmoregulation. Although many studies in fish underline the interconnection between the hypothalamic–pituitary–interrenal (HPI) and hypothalamic–pituitary–thyroid (HPT) endocrine axes, their relationship with vasotocinergic and isotocinergic systems remain unknown. Hence, the aim of the present study is to shed light on the potential cross-regulations between HPT, HPI, and vasotocinergic and isotocinergic axes in gilthead sea bream (Sparus aurata) at hypothalamic, hypophyseal and plasma levels. Sea breams were administered with intraperitoneal slow-release implants containing different doses of vasotocin (the active peptide in vasotocinergic system) or cortisol (the last component of HPI axis). Plasma osmolality was enhanced in Avt treated fish, indicating an osmoregulatory function of this hormone. Low concentrations of Avt increased hypothalamic avt mRNA levels and increased Avt storage in the pituitary. Avt treatment down-regulated hypothalamic avtrv1a, suggesting a negative paracrine co-regulation of the HPI axis due to the close location of avtrv1a and Acth cells in the anterior pituitary. Furthermore, the up-regulation observed in avtrv2 suggests their involvement in metabolic and cortisol-related pathways in the hypothalamus. The decrease in It pituitary storage and the up-regulation of it receptor observed in the Avt-treated group reinforce the idea of an interconnection between vasotocinergic and isotocinergic systems. Cortisol and Avt administration each inhibited the HPI axis, down-regulating crh gene expression in the absence of variations in crhbp. Finally, both hormonal treatments activated the HPT axis via up-regulation of trh and down-regulation of thrb. Our results provide evidence for strong interactions among the Avt/It, HPI and HPT axes of marine teleosts, particularly hypothalamic level.